ECIL guidelines for the diagnosis of Pneumocystis jirovecii pneumonia in patients with haematological malignancies and stem cell transplant recipients - Alanio, Alexandre; Hauser, Philippe M.; Lagrou, Katrien; Melchers, Willem J. G.; Helweg-Larsen, Jannik; Matos, Olga; Cesaro, Simone; Maschmeyer, Georg; Einsele, Hermann; Donnelly, J. Peter; Cordonnier, Catherine; Maertens, Johan; et al. (Journal of antimicrobial chemotherapy, 2016)
The Fifth European Conference on Infections in Leukaemia (ECIL-5) convened a meeting to establish evidence-based recommendations for using tests to diagnose Pneumocystis jirovecii pneumonia (PCP) in adult patients with haematological malignancies. Immunofluorescence assays are recommended as the most sensitive microscopic method (recommendation A-II). Real-time PCR is recommended for the routine diagnosis of PCP (A-II). Bronchoalveolar lavage (BAL) fluid is recommended as the best specimen as it yields good negative predictive value (A-II). Non-invasive specimens can be suitable alternatives (B-II), acknowledging that PCP cannot be ruled out in case of a negative PCR result (A-II). Detecting β-d-glucan in serum can contribute to the diagnosis but not the follow-up of PCP (A-II). A negative serum β-d-glucan result can exclude PCP in a patient at risk (A-II), whereas a positive test result may indicate other fungal infections. Genotyping using multilocus sequence markers can be used to investigate suspected outbreaks (A-II). The routine detection of dihydropteroate synthase mutations in cases of treatment failure is not recommended (B-II) since these mutations do not affect response to high-dose co-trimoxazole. The clinical utility of these diagnostic tests for the early management of PCP should be further assessed in prospective, randomized interventional studies.